"The big sleep: Elucidating the sequence of events in the first hours of death to determine the postmortem interval". Issue 4 (July 2019) - Martínez, Paula Núñez; Menéndez, Sofía T.; Villaronga, María de los Ángeles; Ubelaker, Douglas H.; García-Pedrero, Juana M.; C. Zapico, Sara
Abstract: Recent developments on postmortem interval estimation (PMI) take an advantage of the autolysis process, pointing out to the analysis of the expression of apoptosis and autophagy genes towards this purpose. Oxidative stress plays a role in this signaling as a regulatory mechanism and/or as a consequence of cell death. Additionally, melatonin has been implicated on apoptosis and autophagy signaling, making melatonin a suitable target for PMI determination. The aim of this study was to investigate the early PMI through the analysis of the expression of autophagy genes as well as oxidative stress and melatonin receptor. Our results demonstrated a rapidly increased on the expression of autophagy genes according to the expected sequence of events, then a marked decrease in this expression, matched with the switch to the apoptosis signaling. These results revealed potential candidates to analyze the PMI in the first hours of death, helping to estimate the time-since-death. Highlights: There is a crosstalk between autophagy and apoptosis genes to determine the PMI. Free radicals and melatonin receptor play a key role in these signaling pathways. The role of these biomarkers makes them potential candidates to analyze the PMI. This leads to the development of a novel quantitative method to estimate the PMI.